A comparison of postrelease survival parameters between single and mass stranded delphinids from Cape Cod, Massachusetts, U.S.A. Issue 1 (29th July 2015) - Sharp, Sarah M.; Harry, Charles T.; Hoppe, Jane M.; Moore, Kathleen M.; Niemeyer, Misty E.; Robinson, Ian; Rose, Kathryn S.; Sharp, W. Brian; Landry, Scott; Richardson, Jessica; Moore, Michael J.
Abstract: The viability of healthy single stranded dolphins as immediate release candidates has received little attention. Responders have been reluctant to release lone delphinids due to their social needs, even when they pass the same health evaluations as mass stranded animals. This study tracked postrelease success of 34 relocated and released satellite tagged delphinids from single and mass strandings. Three postrelease survival parameters (transmission duration, swim speed, and daily distance) were examined to evaluate whether they differed among single stranded/single released (SS/SR), mass stranded/single released (MS/SR), or mass stranded/mass released (MS/MR) dolphin groups. Comparisons were also made between healthy and borderline release candidates. Satellite tags transmitted for a mean of 21.2 d (SD = 19.2, range = 1–79), daily distance traveled was 42.0 km/d (11.25, 20.96–70.72), and swim speed was 4.3 km/h (1.1, 2.15–8.54). Postrelease parameters did not differ between health status groups, however, SS/SR dolphins transmitted for a shorter mean duration than MS/MR and MS/SR groups. Postrelease vessel‐based surveys confirmed conspecific group location for two healthy, MS/SR dolphins. Overall, these results support the potential to release healthy stranded single delphinids; however, further refinement of health assessment protocols for these challenging cases is needed.